UJI EFEK PENYEMBUHAN LUKA SEDIAAN GEL EKSTRAK ETANOL DAUN AFRIKA (VERNONIA AMYGDALINA.DEL) PADA MENCIT JANTAN - Ernawaty, Ernawaty; Bintarti, Tri; Handayani, Maya (Politeknik Kesehatan Kemetrian Kesehatan Medan, 2014)
African leaf (Vernonia amygdalina) is one of the potent plants as antidiabetic, antibacterial,antifungal, analgesic and antioxidant. The aims of this study was to determine the wound healingeffect of ethanolic extract of african leaves gel and obtain an effective formula. It was an experimentalresearch. Injuries were made by cutting the back of mice’s skin with diameter ± 1 cm. Fourty eightmice were divided into 8 groups, one group as control, EEDA 1%, EEDA 3% , EEDA 5%, EEDA 7%,EEDA 9% , Bioplacenton as positif control and base gel group. The observation was done bymeasured the diameter of wound visually. The mice declared cure and marked growth of new skin andhair around the wound. At the end of the test performed histophatological test. This study concludedthe ethanol extract of Africa leaves have wound healing effect in mice and EEDA 9% have woundhealing effect at 15th daya.